Photoionization of Ne Atom Ions in the Framework of the Modified Atomic Orbital Theory - Sakho, I. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
We report accurate resonance energies and width of the 1s2s\({}^{2}\)p\({}^{6}\)np \({}^{1}\)P\({}^{1}\) and 1s\({}^{2}\)2s2p\({}^{6}\)np \({}^{1}\)P\({}_{1}\) series of Ne neutral atom. Calculations are performed in the framework of the Modified atomic orbital theory (MAOT). Excellent agreements is obtained with high synchrotron radiation measurements of Schulz et al. [Phys. Rev. A 54, 3095 (1996)] and of Muller et al. [Astrophys. J. 836, 166 (2017)]. The high lying accurate resonance energies tabulated may be benchmarked data for interpreting spectra lines of Ne neutral atom from astrophysical objects.